MIGRASI TENAGA KERJA PEDESAAN DAN POLA PEMANFAATANNYA - JULIA FORCINA SINURAYA; SAPTANA - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
Economic development is a dynamic process in medium or long term that bringsimpact on social economics’ structural change in rural community. The social economictransformation can be as sectoral shiftment or employment, institutional, and norms amongwherein community. Macro data assessment shows that sectoral economic shifts faster thanemployment shiftment. The objective of this paper is to analyze: (1) Macro Employment;(2) Migration scheme of rural labor; (3) Identification activity type in the origin; (4) Drivenand apathetic factors of rural labor migration; and (5) The utility scheme of migration inhousehold economy. Macro description (1990 – 2005) on population migration in threerepresentative provinces shows that immigration less than emigration. In general view ofthat, population move consistently from producer area of agricultural product in the rural tourban area. There two schemes of representative rural migration. Migration scheme in wetland area is seasonal, while one in dry land tends to be constant. The aggregate shows thatmain driven factor of household member to migrate in two type of agro ecosystem is thelimited employment in rural area; in contrary apathetic factors in destination area is higheropportunity of job. Living cost payment is major utility scheme that resulted of householdmember migration, particularly for household consumption, school fee, house renovation,and saving.